Study of Landslide Susceptibility on Geotechnic and Soil Hydrological Characteristics - Marchel Maxy Rijoly; Pieter Jozef Kunu; Rafael Martinus Osok (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2026)
This study aims to analyze the physical, geotechnical, hydrological, and mineralogical properties of soil, as well as the presence of slip surfaces and their influence on the landslide potential of